Remembering and Forgetting a Political Place: Tito's Birthplace in Everyday Usage - Škrbić Alempijević, Nevena (2009)
The aim of this paper is to analyze how memory of the socialist past is dealt with in postsocialist Croatia. Furthermore, the author raises the question of the construction and deconstruction of political places. This topic is discussed through the case study of Kumrovec as the birthplace of the former Yugoslav president Josip Broz Tito and especially through the prism of local inhabitants.
Projekt MZOS
ENG